Practical approach to criminal procedure - Sprack, John; Sprack, Michael (Oxford : Oxford University Press, $c, 2015)
This edition is a guide to the criminal process in England and Wales, from the start of criminal proceedings and the first court appearance of the accused, through to sentencing and appeal.
Setting the scene -- The role of the criminal procedure rules -- Preliminaries to court appearance -- Prosecutors -- The decision to prosecute -- Magistrates and their courts -- Bail and remands -- Mode of trial -- Disclosure -- Course of a summary trial -- Trial of juveniles -- Committal for sentence -- Sending cases to the crown court -- Trial on indictment -- The Crown Court -- The Indictment -- Pre-trial proceedings -- Pleas -- The jury -- Judge-only trials -- The course of the trial -- The verdict -- Sentencing -- Procedure before sentencing -- Determining the sentence -- Custodial sentences -- Sentences other than custody -- Appeals from the crown court -- Appeals from the magistrates' courts -- The European dimension -- Ancillary financial matters -- Your practice
Previous edition: 2012.
Includes bibliographical references and index.
Keywords: Criminal procedure -- England; Criminal procedure -- Wales; Criminal procedure; England; Wales